Trump and the Deglobalization of the United States and Latin America - LUQUE BRAZÁN, José; JIJON MAGANDA , Néstor; PÉREZ TAGLE, Jesús (Utopía y Praxis Latinoamericana, 2025)
The objective of this essay is to examine the reconfiguration of the right and left in the American continent. The beginning of the political and cultural battle between the projects of the libertarian political elites (extreme right) and the political projects of the left-wing spectrum in the region (progressives, neo/revolutionary nationalists, socialists and Marxists) is theorized, as a result of the failure of the neoliberal globalization whose roots are found in the political legacy of Margaret Thatcher and Ronald Reagan and the proposals of Von Hayek. In this sense, it is assumed that the presidential election of Donald Trump, Javier Milei, Nayib Bukele and Jair Bolsonar (from the extreme right), and Claudia Sheinbaum, Ignacio Lula Da Silva, Gustavo Preto and Yamandú Orsi (from the left), are fundamental pieces in the probable political conflict to come, when Trump becomes president of the United States. Methodology used: Documentary analysis of scientific and public opinion sources. Time cut: 2016 – 2024, because Trump assumes his first presidential term in 2016 and is re-elected in 2024.